Hacia una regulación ética y sostenible de la inteligencia artificial en Colombia - Vargas-Chaves, Iván (Law, State and Telecommunications Review, 2025)
[Purpose] This paper aims to critically analyze the bill "by means of which artificial intelligence is regulated in Colombia to ensure its ethical and sustainable development," proposed on May 7, 2025, which seeks to harmonize technological innovation with the protection of fundamental rights and sustainable development. [Methodology] To achieve the objective, a qualitative documentary analysis methodology was used, centered on the bill. This was complemented by academic literature, OECD/UNESCO reports, and comparative frameworks, found through strategic searches (databases, keywords, Boolean operators). The documents were critically analyzed, contrasting them with international references, to synthesize critical factors, challenges, and impact in Colombia. [Findings] It is demonstrated that, although the bill presents a robust structure aligned with international standards, its success will depend on overcoming challenges, institutional capacity, and adaptation to the national context. The results also highlight strengths such as the risk-based approach and ethical principles, but also point out crucial challenges in definitions, funding, and in guaranteeing other recognized rights and interests. The main conclusion is that the bill is a valuable milestone for Colombia. However, the materialization of an ethical and inclusive digital future through artificial intelligence requires careful implementation, adequate funding, political will, and active social participation, to ensure that the adaptation of international models is effective and benefits all Colombian society.